2019
DOI: 10.2139/ssrn.3416095
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Efficiency of Public Hospitals in Kuwait: A Two-Stage Data Envelopment Analysis and a Qualitative Survey Study

Abstract: The recent drop in oil prices has challenged public sector financing in Kuwait. Technical and scale efficiency scores for fifteen public hospitals in Kuwait from 2010 to 2014 were estimated using a two-stage data envelopment analysis (DEA). Technical efficiency scores were regressed against institutional characteristics using Tobit regression to investigate the determinants of efficiency differences in hospitals. Semi-structured interviews were also carried out with fourteen public and private hospital manager… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…The results are consistent with previous studies (e.g., Habib and Shahwan, 2020;Top et al, 2020;William et al, 2020;Ilgun and Konca, 2019;Plasschaert, 2018;Al-Refaie et al, 2017;Wang et al, 2016). They suggested that managers and policymakers could be relying on the most important variables (beds and nurses) in making (Alsabah et al, 2020) whereas nurses have an insignificant effect on efficiency. Consistent with previous studies (e.g.…”
Section: Determinants Of Isolation Hospitals Efficiencysupporting
confidence: 92%
See 2 more Smart Citations
“…The results are consistent with previous studies (e.g., Habib and Shahwan, 2020;Top et al, 2020;William et al, 2020;Ilgun and Konca, 2019;Plasschaert, 2018;Al-Refaie et al, 2017;Wang et al, 2016). They suggested that managers and policymakers could be relying on the most important variables (beds and nurses) in making (Alsabah et al, 2020) whereas nurses have an insignificant effect on efficiency. Consistent with previous studies (e.g.…”
Section: Determinants Of Isolation Hospitals Efficiencysupporting
confidence: 92%
“…DEA has been extensively used by researchers and practitioners to evaluate hospital performance and in measuring the efficiency of various types of healthcare organizations including public hospitals (Alsabah et al, 2020;Ngobeni et al, 2020;Najadat et al, 2020;Kocisova et al, 2018;Almiman, 2018;Mitropoulos et al, 2015;Mogha et al, 2015;Najadat and Alsmadi, 2011;Akazili et al, 2008), university and research hospitals (Akkan et al, 2020;Ilgun and Knoca, 2019;Bahrami et al, 2018;Chowdhury and Zelenyuk, 2016) and private hospitals (Habib and Shahwan, 2020;Gandhi and Sharma, 2018;Mogha et al, 2012). Ngobeni et al (2020) measured the technical efficiency of public hospitals in nine provinces in South Africa based on CRS and VRS-DEA during the period 2017-2018.…”
Section: Operational Efficiency Of Isolation Hospitalsmentioning
confidence: 99%
See 1 more Smart Citation
“…This calls into question how well private hospitals perform in comparison to public hospitals. Researchers have extensively employed DEA to analyze hospital performance and measure the e ciency of various types of healthcare organizations, including public hospitals [29][30][31][32][33][34] and private hospitals [35][36][37][38].…”
Section: Literature Reviewmentioning
confidence: 99%
“…If we begin evaluating the effectiveness of the financing function or Kuwait's health financing policies, we can see that by 2019, the current health expenditure in Kuwait as a percent of GDP was 5.5 percent; that corresponds to a 7.77 percent increase from the previous year in 2018 and maintains the positive percent change consistently found through the years -except for the minor dip in 2017 that indicates a -1.64 percent reduction from 2016; nevertheless, as displayed in Table 1 and Figure 1 [4], [5], the overall trend of the line graph suggests consistent increase before 2015 but continues to climb again after 2015 with a positive percent change of almost 40 percent between 2015-2019. This study will provide the necessary research to establish a difference in cost-effectiveness and quality of services; furthermore, this paper can contribute to the data and our later understanding and knowledge of the economic issues arising from increased healthcare costs.…”
Section: Introductionmentioning
confidence: 99%